2015
DOI: 10.1007/s00417-015-3175-z
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of macular edema in eyes with branch retinal vein occlusion changes the diameter of unaffected retinal vessels

Abstract: Unaffected retinal venular diameters associate with the course of BRVO with ME. This may help elucidate the pathological mechanism underlying BRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…We found negligible changes in the areas of the major retinal arteries following anti-VEGF therapy. These findings are consistent with those reported by Im et al, who observed unremarkable changes in the artery diameters during a long-term follow-up after anti-VEGF therapy [ 26 ]. It is supposed that the thick artery walls showed increased resistance to the vasoconstrictive effect of anti-VEGF therapy [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found negligible changes in the areas of the major retinal arteries following anti-VEGF therapy. These findings are consistent with those reported by Im et al, who observed unremarkable changes in the artery diameters during a long-term follow-up after anti-VEGF therapy [ 26 ]. It is supposed that the thick artery walls showed increased resistance to the vasoconstrictive effect of anti-VEGF therapy [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with those reported by Im et al, who observed unremarkable changes in the artery diameters during a long-term follow-up after anti-VEGF therapy [ 26 ]. It is supposed that the thick artery walls showed increased resistance to the vasoconstrictive effect of anti-VEGF therapy [ 26 , 27 ]. Accordingly, we calculated the P/A ratios in our study to reduce the possible influence of the variability in the branches of retinal arteries.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of treatment on the microvasculature in those with RVO have also been assessed. A relative venodilation of unaffected vessels during recent branch RVO has been demonstrated, which is theorized to occur due to increased venous flow in the patent vessels and by concurrent nitric oxide and VEGF dependent mechanisms driven by the ischaemic retina . Clinic‐based studies have shown that the development of macular oedema in eyes with RVO results in retinal venodilation compared to those without macular oedema .…”
Section: Retinal Venular Occlusionmentioning
confidence: 99%
“…A relative venodilation of unaffected vessels during recent branch RVO has been demonstrated, which is theorized to occur due to increased venous flow in the patent vessels and by concurrent nitric oxide and VEGF dependent mechanisms driven by the ischaemic retina . Clinic‐based studies have shown that the development of macular oedema in eyes with RVO results in retinal venodilation compared to those without macular oedema . Treatment of macular oedema with intra‐vitreal anti‐VEGF agents or argon laser photocoagulation has showed that these treatments reverse the effects of hypoxia and other vaso‐active mediators; resulting in both arteriolar and venular constriction .…”
Section: Retinal Venular Occlusionmentioning
confidence: 99%
See 1 more Smart Citation